2019
DOI: 10.1021/acsabm.9b00123
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Enzymatic Cleavage of DNA through Supramolecular Chiral Induction to a Cationic Polythiophene

Abstract: Water-soluble π-conjugated polymers are increasingly envisioned in biosensors, in which their unique optical and electronic properties permit a highly sensitive detection of biomolecular targets. In particular, cationic π-conjugated polymers are attractive for DNA sensing technologies, through the use of the fluorescence signals either in physiological solutions or in thin films. However, in the context of enzymatic activity assays, fluorescence-based methods require covalently labeling DNA with a dye or an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Previously, we showed that the P3HTÀ PMe 3 binding to DNA induces a rearrangement in the distribution of the dihedral angles between thiophene units, from a slight majority of anti configurations between thiophene units (for the pure polymer) to a majority of syn configurations when it interacts with DNA. [14] The change toward a syn P3HTÀ PMe 3 backbone is also observed in each replica of this study. Interestingly, the ratio of syn-to anti-dihedral angles is very similar between the four replicas ( Table 1).…”
Section: A Preserved Geometrical Pattern: Syn or Anti Blockssupporting
confidence: 65%
See 3 more Smart Citations
“…Previously, we showed that the P3HTÀ PMe 3 binding to DNA induces a rearrangement in the distribution of the dihedral angles between thiophene units, from a slight majority of anti configurations between thiophene units (for the pure polymer) to a majority of syn configurations when it interacts with DNA. [14] The change toward a syn P3HTÀ PMe 3 backbone is also observed in each replica of this study. Interestingly, the ratio of syn-to anti-dihedral angles is very similar between the four replicas ( Table 1).…”
Section: A Preserved Geometrical Pattern: Syn or Anti Blockssupporting
confidence: 65%
“…In a previous study, we proposed a stable binding mode of P3HTÀ PMe 3 around a double-stranded DNA, with preferential adsorption of the thiophene units along the DNA minor-groove, and with the lateral phosphonium groups complexed by the DNA phosphodiester groups. [14] To uncover other stable binding modes, we performed four new MD replicas (named R1 to R4), from 2 μs to 10 μs, see the Methods Section. We follow the time-evolution of the distance between the centers of mass (COM) of both partners (Figure 1), as an average indicator of DNA/polymer proximity within the complexes.…”
Section: Structural Aspects Of Dna/polymer Assembliesmentioning
confidence: 99%
See 2 more Smart Citations
“…These signals were utilized notably to monitor the enzymatic cleavage of DNA. This supramolecular approach allowed the researchers to detect the enzymatic activity in a continuous, label‐free manner . Others reported the use of fluorescence signals of conjugated polymers to detect single‐nucleotide polymorphisms and DNA damages, using dye‐labeled DNA …”
Section: Towards Functional Self‐assembliesmentioning
confidence: 99%